2018
DOI: 10.1055/a-0579-9050
|View full text |Cite
|
Sign up to set email alerts
|

ESD versus EMR in non-ampullary superficial duodenal tumors: a systematic review and meta-analysis

Abstract: Background and study aims  Endoscopic submucosal dissection (ESD) has been developed as an option for treatment of esophageal, gastric and colorectal lesions. However, there is no consensus on the role of ESD in duodenal tumors. Methods  This systematic review and meta-analysis compared ESD and endoscopic mucosal resection (EMR) in sporadic non-ampullary superficial duodenal tumors (NASDTs), including local experience. We conducted a search in PubMed, Scopus and the Cochrane library up to August 2017 to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
(127 reference statements)
1
37
0
Order By: Relevance
“…In a recent large retrospective Japanese study involving 168 patients, the rate of delayed adverse events after duodenal ESD was significantly reduced when the mucosal defect was completely closed, compared with only partial closure or no closure (1.7 % vs. 25 % vs. 15.6 %, respectively, P < 0.01) [115]. These data were confirmed by two more studies where delayed bleeding was effectively prevented by prophylactic endoscopic closure of the defect [18,116]. Recently, closure of the defect by OTS clipping has also been shown to be effective in reducing delayed adverse events after ESD [117].…”
Section: Prevention Of Delayed Adverse Events After Duodenal Endoscopic Resectionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a recent large retrospective Japanese study involving 168 patients, the rate of delayed adverse events after duodenal ESD was significantly reduced when the mucosal defect was completely closed, compared with only partial closure or no closure (1.7 % vs. 25 % vs. 15.6 %, respectively, P < 0.01) [115]. These data were confirmed by two more studies where delayed bleeding was effectively prevented by prophylactic endoscopic closure of the defect [18,116]. Recently, closure of the defect by OTS clipping has also been shown to be effective in reducing delayed adverse events after ESD [117].…”
Section: Prevention Of Delayed Adverse Events After Duodenal Endoscopic Resectionmentioning
confidence: 82%
“…Similarly, increasing lesion size was associated with a higher recurrence rate [19,52,55,63,106]. With regard to the techniques originally used to remove the lesion, no significant difference in recurrence rate was observed between EMR versus ESD or EMR versus hybrid ESD [18,81]. After a median follow-up of 6.5 months (2-125), Pérez-Cuadrado-Robles et al [20] showed 5/37 recurrences (14.7 %) after ESD and 17/129 (16.7 %) after EMR (P = 0.788).…”
Section: Prevention Of Delayed Adverse Events After Duodenal Endoscopic Resectionmentioning
confidence: 92%
“…Published data on duodenal ESD in the West is extremely limited. Pérez-Cuadrado-Robles et al 27 published a metanalysis and systematic review of the current published literature that included 14 studies, but only 2 were from the West. Similar rates of bleeding and perforation were found in the East and West.…”
Section: Endoscopic Submucosal Dissection In Duodenummentioning
confidence: 99%
“…A 2018 meta-analysis included 14 studies to compare duodenal ESD versus EMR for a total of 784 nonampullary superficial duodenal tumors with the main outcome measure of including en bloc resection. 5 It is worth while to note that only 2 of these studies 5,6 were performed outside of Asia. Although ESD provided a higher complete resection rate (odds ratio [OR], 1.63; 95% confidence interval [CI], 1.06-2.5; P Z .03), there was an increased risk of intraoperative perforations (risk difference, 0.12; 95% confidence interval, 0.04-0.20; P Z .002) and emergent surgery for delayed perforations.…”
mentioning
confidence: 99%
“…Specifically, there were 41 out of 238 (17.2%) ESD versus 8 out of 536 (1.49%) EMR intraoperative perforations and 8 out of 236 (3.39%) ESD versus 2 out of 536 (0.37%) EMR delayed perforations. 5 The meta-analysis concluded that given the higher perforation rates, further prospective or controlled studies were needed before duodenal ESDs could be conclusively supported.…”
mentioning
confidence: 99%